EFEKTIVITAS WHOLE BRAIN WRITING GAME DALAM PEMBELAJARAN WRITING - Ernadewi Kartikasari, Lusiana Dewi Kusumayati (Widya Wacana: Jurnal Ilmiah, 2018)
AbstractThis research is an experimental study which was implemented to find out the significance difference of students’ writing skill when they were taught using Whole Brain Writing Game. The design of this research is Quasi-experimental using pre-test post test and control group. This research was conducted in grade VIIC and VIID SMP N 7 Surakarta. Grade VIIC was used as experimental class while VIID was used as control class. Both classes were taught using the same topic and time period but using different method. Experimental was taught using Whole Brain Writing Game, while control class was taught using Direct Instruction Method. In collecting data, the researcher used pre-test and post test. The data were analyzed using t-test formula to know the effectiveness of the treatment given in experimental class. The result of t-test calculation showed that to = 1.60 is lower than tt (62, 0.05) = 1.67. The null hypothesis (Ho) was accepted. It means that there was no significance difference on the students taught using Whole Brain Writing Game (WBWG) and students who were taught using Direct Instruction Method (DIM). Even though the result of their mean scores are not significantly different, the students taught using WBWG had better writing achievement with mean score 74.34 while mean score in control class 71.16. The difference of the mean scores was 3.18. It can be concluded that the writing skill of students taught using Whole Brain Writing Game is not significantly difference from the students taught using Direct Instruction Method even though from the result of mean score, students who were taught using Whole Brain Writing Game having better writing achievement than those who were taught using Direct Instruction Method.Key words: Whole Brain Writing Game, Teaching Writing, Experimental Research  AbstrakPenelitian ini merupakan penelitian experimental yang dilaksanakan untuk mengetahui perbedaan signifikan kemampuan writing siswa yang diajar menggunakan metode Whole Brain Writing Game. Desain yang digunakan dalam penelitian ini adalah Quasi-Experimental dengan menggunakan pre-test-post test dan control grup. Penelitian ini dilaksanakan di kelas VIIC dan VIID SMP Negeri 7 Surakarta. Kelas VIIC digunakan sebagai kelas experimental sedangkan kelas VIID digunakan sebagai kelas kontrol. Kedua kelas tersebut diajarkan dengan menggunakan topik dan periode waktu  yang sama tetapi menggunakan metode yang berbeda, kelas experimen menggunakan Whole Brain Writing Game sedangkan kelas kontrol menggunakan Direct Instruction Method. Dalam mengumpulkan data, peneliti menggunakan pre test dan post test. Data yang didapat kemudian dianalisis dengan menggunakan t-test formula untuk mengetahui efektivitas treatment yang diberikan di kelas experiment. Hasil penghitungan t-test menunjukkan bahwa to = 1.60 lebih rendah dari tt (62, 0.05) = 1.67. Dengan demikian null hypothesis (Ho) diterima yang berarti bahwa tidak terdapat perbedaan yang signifikan antara siswa yang diajar menggunakan metode Whole Brain Writing Game (WBWG) dengan siswa yang diajar menggunakan Direct Instruction Method. Meskipun tidak terdapat perbedaan yang signifikan, siswa yang diajar dengan menggunakan WBWG memiliki kemampuan yang lebih baik dengan nilai rata-rata 74.34 sedangkan nilai rata-rata kelas control 71.16. Perbedaan antara keduanya sebesar 3.18. Dengan demikian dapat disimpulkan bahwa kemampuan writing siswa yang diajar menggunakan Whole Brain Writing Game tidak memiliki perbedaan yang signifikan dengan siswa yang diajar menggunakan Direct Instruction Method meskipun  berdasarkan hasil nilai rata-rata mereka, siswa yang diajar dengan menggunakan metode Whole Brain Writing Game memiliki kemampuan menulis yang lebih baik daripada siswa yang diajar menggunakan Direct Instruction Method.Kata Kunci:     Whole Brain Writing Game, Pembelajaran Writing, Penelitian Eksperimental